Bahaya Social Engineering dalam Sosial Media - Sri Utami; Dina Afifah; Masduki Asbari (Literaksi: Jurnal Manajemen Pendidikan, 2023)
The purpose of this research is to explain how the dangers of Social Engineering in using social media. In this study, a qualitative approach was used using the see note method, which was sourced from the Youtube channel (Diskusi Bersama Sabrang MDP) entitled "Filters in social media posts". The results of a brief review of the process of listening to this study are about how we can be wise and careful in posting something on social media. The behavior of posting photos, videos or writing that contains personal information can put users in a dangerous position and have the potential to lose user privacy. Many of the crimes are committed with the aim of gaining profit. The perpetrator took photos and telephone number information of the victim through social media and edited the victim's photo into a vulgar photo to threaten and blackmail the victim. Cases of misuse of information are caused by a lack of awareness to maintain the privacy of information on social media. Social engineering is a technique that needs to be watched out for in maintaining information security. Social Engineering focuses on the weakest part of the computer network system, namely humans. The technique seeks to retrieve personal information by carrying out psychological manipulation through social interaction mechanisms. In addition, in the implementation of social engineering, the perpetrator asks directly for what he wants.